The Model Development of Professional Competence of Methodists of Extracurricular Institutions - Natalia Davydiuk (Pedagogical Discourse, 2012)
Characteristic of levels of forming of Ukrainian-speaking dialogue competence of the pupils of 10-11 forms of general schools is offered in the article, external and internal factors, influencing the effectiveness of forming of Ukrainian-speaking dialogue competence are presented.